Peran Ekonomi Kreatif Dalam Meningkatkan Pendapatan UMKM Pusat Grosir Solo di Masa Pandemi Covid-19 - Dhany Prasetyo; Ismunawan Ismunawan (Mandiri : Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the role of the creative economy in increasing the income of MSMEs at the Solo Wholesale Center during the Covid-19 pandemic. This study applies a qualitative descriptive approach. Data collection techniques apply interview, observation, and documentation techniques. The data analysis method uses an interactive model consisting of four steps of analysis, namely data collection, presentation, data reduction, and drawing conclusions. The results of the study show that the creative economy implemented by traders at PGS Solo has a positive influence on business continuity, although the increase in income obtained has not been able to cover the decrease in income felt during the Covid-19 pandemic. The creative economy is able to foster enthusiasm and optimism to survive and rise in running a business during the Covid-19 pandemic.